Active faults paragenesis and the state of crustal stresses in the Late Cenozoic in Central Mongolia - V. A. Sankov; A. V. Parfeevets; A. I. Miroshnichenko; A. V. Sankov; A. Bayasgalan; D. Battogtokh (Геодинамика и тектонофизика)
Active faults of the Hangay-Hentiy tectonic saddle region in Central Mongolia are studied by space images interpretation, relief analysis, structural methods and tectonic stress reconstruction. The study results show that faults activation during the Late Cenozoic stage was selective, and a cluster pattern of active faults is typical for the study region. Morphological and genetic types and the kinematics of faults in the Hangay-Hentiy saddle region are related the direction of the ancient inherited structural heterogeneities. Latitudinal and WNW trending faults are left lateral strike-slips with reverse or thrust component (Dzhargalantgol and North Burd faults). NW trending faults are reverse faults or thrusts with left lateral horizontal component. NNW trending faults have right lateral horizontal component. The horizontal component of the displacements, as a rule, exceeds the vertical one. Brittle deformations in fault zones do not conform with the Pliocene and, for the most part, Pleistocene topography. With some caution it may be concluded that the last phase of revitalization of strike slip and reverse movements along the faults commenced in the Late Pleistocene. NE trending disjunctives are normal faults distributed mainly within the Hangay uplift. Their features are more early activation within the Late Cenozoic and the lack of relation to large linear structures of the previous tectonic stages. According to the stress tensor reconstructions of the last phase of deformation in zones of active faults of the Hangay-Hentiy saddle using data on tectonic fractures and fault displacements, it is revealed that conditions of compression and strike-slip with NNE direction of the axis of maximum compression were dominant. Stress tensors of extensional type with NNW direction of minimum compression are reconstructed for the Orkhon graben. It is concluded that the activation of faults in Central Mongolia in the Pleistocene-Holocene, as well as modern seismicity were controlled mainly by additional horizontal compression in the SW direction, which was associated with convergence of the Indian subcontinent and Eurasia. The influence of the asthenosphere flow in the SE direction at the base lithosphere is an additional factor facilitating strike-slip deformation of the crust in the study area and a possible explanation of divergent movements in the Baikal Rift, as well as the SE movement of the Amur plate. The Eastern Hangay crust is deformed under extension associated with a dynamic impact of the local mantle anomaly on the lithosphere. The boundary between the Amur plate and the Mongolian block (according to [Zonenshain, Savostin, 1979]) is fragmentary expressed in the tectonic structure. It represents a rim part of the deformation zone, embracing the Mongolian block and the adjacent uplifts of the Mongolian Altai, Tuva and Eastern Sayan. Along the boundary, compressive and transpressive strain occurred in the Pleistocene-Holocene.